Strategi Pengelolaan Kelas Outdoor Sebagai Penunjang Pembelajaran Kontekstual - Mubtadiatul Faizah; Ave Vania Martha; Fanny Zahrotun Nadhifa; Muhammad Nofan Zulfahmi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research aims to explore outdoor classroom management strategies as an effective contextual learning approach in increasing student motivation and learning outcomes. The method used is qualitative research, library research, by collecting data from books, scientific journals and related articles. Data analysis was carried out descriptively to formulate concepts and strategies for implementing outdoor learning. The research results show that outdoor classes can increase students' mental and physical engagement, encourage the development of critical thinking skills, collaboration, and character traits such as responsibility and concern for the environment. Outdoor learning also helps students connect theoretical concepts with real experiences. Although the benefits are significant, challenges such as weather, limited facilities, and lack of teacher skills need to be addressed through teacher training, contingency planning, and collaboration with local communities. Comprehensive evaluation and the use of triangulation methods can increase teachers' understanding of student learning outcomes. With the right support, outdoor classes can be an innovative and sustainable learning strategy that supports the formation of an intelligent and adaptive generation.